2023
DOI: 10.1108/ijbm-10-2022-0439
|View full text |Cite
|
Sign up to set email alerts
|

Counteracting dark sides of robo-advisors: justice, privacy and intrusion considerations

Abstract: PurposeUnder the pressure of dynamic business environments, firms in the banking and finance industry are gradually embracing Fintech, such as robo-advisors, as part of their digital transformation process. While robo-advisory services are expected to witness lucrative growth, challenges persist in the current landscape where most consumers are unready to adopt and even resist the new service. The study aims to investigate resistance to robo-advisors through the privacy and justice perspective. The human-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…They found that robo-analysts do not have human biases such as overoptimism or representativeness, but not all of their recommendations are profitable. An alternative to the technology-recognition paradigm was explored by Aw et al (2023) using surveys to investigate the reasons for customer resistance to roboadvisors. They reported that perceived fairness, intrusiveness and invasion of privacy are the main drivers of consumer resistance to the technology.…”
Section: Human Behaviourmentioning
confidence: 99%
“…They found that robo-analysts do not have human biases such as overoptimism or representativeness, but not all of their recommendations are profitable. An alternative to the technology-recognition paradigm was explored by Aw et al (2023) using surveys to investigate the reasons for customer resistance to roboadvisors. They reported that perceived fairness, intrusiveness and invasion of privacy are the main drivers of consumer resistance to the technology.…”
Section: Human Behaviourmentioning
confidence: 99%
“…Kim and Kim, 2018). This study follows the latter stream of research to define perceived justice with AI as consumers' subjective judgment about the degree of justice they expect while using an AI-enabled offering (Aw et al, 2023;Seiders and Berry, 1998). Consumers' justice perceptions about AI are formed throughout the pre-, during, and post-consumption stages (Singh and Crisafulli, 2016) through their own experiences or by encountering company's ads or policy pages (Kukar-Kinney et al, 2007), and get refined over time (Wirtz and Lwin, 2009).…”
Section: Justice Theorymentioning
confidence: 99%
“…Apart from AI's accountability, consumer perceptions of AI's expertise (a dimension of AI credibility) also affect their delegation experience positively (Lubars and Tan, 2019). AI's customizability (a subdimension of AI credibility) can help maintain consumers' autonomy, thus avoiding making them feel replaced in the delegation experience (Aw et al, 2023;Sajtos et al, 2020).…”
Section: Ai Credibility and Consumer-ai Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the final article, Aw et al (2024) examine the resistance to the adoption of robo-advisors in their study, specifically from the perspectives of justice and privacy. This study complements past research that predominantly focused on the technology acceptance paradigm.…”
mentioning
confidence: 99%